Matan Jazariyyah Learning Model in Improving Al-Qur'an Tahsin Ability - Hamid, Abdul; Rayamangsi; Hakim, Abdul; Sain, Muhammad (Al-Ulum, 2024)
This study examines the model of learning matan jazariyah and its implications for improving the ability of tahsin Al-Quran in students at PTQ Darussaqqaf Polman. The type of research is qualitative, case study approach, and constructivism paradigm. Data sources are leaders, ustadz-ustadzah, and students. Data analysis techniques use grounded theory through three stages, namely open coding, axial coding, and selective coding. The results show that, the implementation of tajwid learning through a systematic and structured halaqah method, combining memorization, theory, and practice, is carried out in groups every after Fajr. The implications of learning matan jazariyyah can improve the ability to read the Qur'an fluently, according to good and correct tajwid rules, thereby improving the quality of tahsin students. The development model of learning Matan Jazariyyah refers to the halaqah model developed into Halaqah Matan Jazariyyah which emphasizes the deepening of tajwid material in a structured manner, direct practice, and evaluation of memorization and reading of the Qur'an. The Halaqah Matan Jazariyyah approach is more transformative because it prioritizes memorization of the Qur'an and a deep understanding of the rules of tajwid.